Avaliação e reorganização curricular: uma experiência no curso de odontologia - Crepaldi, Maria de Lourdes Silva (2007)
The object of this work is constituted in identifying the focuses which are the obstacles of the curriculum development and search for ways to the curriculum reorganization of the Odontology course at the University of Cuiabá-MT. It was an intention to limit the analysis to some academic focuses, in an outline able to characterize only the didactic-methodological aspects. The aim was to contribute to the Institutional Evaluation of the University with the results of the evaluationreorganization of the Course being studied, searching for an emancipatory curriculum. The investigation consisted of an action-research characterized by the intervention which leads to integrated action, to getting competence for action, to building viable alternatives to the auto-regulation and to the transforming practice of the university life. The analysis of the documents, interviews, questionnaires, small committees, seminars, Lafourcade s curriculum indicative table of areas and Smyth s table (1991, p. 122) for the process of critical reflection on the teaching practice, in classes, were the used procedures. The observed results took place in the teacher s low pedagogical knowledge; the closed, little flexible disciplinary curriculum organization type, the teachers initial non-involvement in the research and consequently with the continued education; Unic s involvement with the social actions, which has been contributing to the professional citizen formation, although bigger emphasis should be given to this purpose, when specifically treating the curriculum reorganization with emancipatory perspective